LINGUISTIC AND CULTURAL FEATURES OF RIDDLES (ON THE BASIS OF RUSSIAN, UZBEK AND ENGLISH LANGUAGES) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article analyzes one of the most alternative linguistic and cultural features of riddles and reveals the importance of riddles among the languages in the research. The article can definitely help to get enough information about riddles for students and researchers in education. By comparing three languages we can reveal the main differences of riddles in linguistic and cultural sides.